The impact of COVID-19-induced distance learning on physical activity and dietary habits of female students in the Qassim Region - Mona S. Almujaydil (Journal of Family Medicine and Primary Care)
Background: The COVID-19 pandemic has profoundly affected the physical activity (PA) levels and dietary habits of individuals, particularly children and adolescents in Saudi Arabia, owing to widespread closures and social distancing measures, including school closures. Methods: A cross-sectional study was conducted to assess the impact of distance learning (DL) on PA and dietary habits among public middle school girls during the pandemic. The Arab Teens Lifestyle Questionnaire (ATLS) was used to assess habitual PA, sedentary behavior, and dietary habits. Results: A total of 300 middle school female students, with an average age of 14 years, participated in the study. The results indicated a generally low level of PA among students during DL and after school reopening, with a significant decrease in specific types of PA, such as walking and stair climbing during DL. However, after schools reopened, there was a significant increase in students’ participation in activities such as swimming, dancing, and housework (P < 0.05). Moreover, sleep hours and TV-watching time increased compared to the DL period. Despite the prevalence of students frequently consuming soft drinks, sugary treats, fried and fast foods, as well as sweets and chocolates during the lockdown, middle school girls also consumed a lot of fruits and vegetables. Conclusion: Assessing students’ habitual PA and dietary habits during the lockdown may provide insights into their future health and well-being post-pandemic. This assessment can help in identifying strategies to redirect current PA levels to maintain health and prevent potential long-term health implications.